Probing plant membranes with FM dyes: tracking, dragging or blocking? - Jelínková, Adriana; Malínská, Katerina; Simon, Sibu; Kleine-Vehn, Jürgen; Parezová, Markéta; Pejchar, Premysl; Kubes, Martin; Martinec, Jan; Friml, Jirí; Zazímalová, Eva; Petrásek, Jan (The Plant journal, 2010)
Remarkable progress in various techniques of in vivo fluorescence microscopy has brought an urgent need for reliable markers for tracking cellular structures and processes. The goal of this manuscript is to describe unexplored effects of the FM (Fei Mao) styryl dyes, which are widely used probes that label processes of endocytosis and vesicle trafficking in eukaryotic cells. Although there are few reports on the effect of styryl dyes on membrane fluidity and the activity of mammalian receptors, FM dyes have been considered as reliable tools for tracking of plant endocytosis. Using plasma membrane-localized transporters for the plant hormone auxin in tobacco BY-2 and Arabidopsis thaliana cell suspensions, we show that routinely used concentrations of FM 4-64 and FM 5-95 trigger transient re-localization of these proteins, and FM 1-43 affects their activity. The active process of re-localization is blocked neither by inhibitors of endocytosis nor by cytoskeletal drugs. It does not occur in A. thaliana roots and depends on the degree of hydrophobicity (lipophilicity) of a particular FM dye. Our results emphasize the need for circumspection during in vivo studies of membrane proteins performed using simultaneous labelling with FM dyes.
Keywords: fluorescenční barviva; Quaternary Ammonium Compounds; Cell Line; pyridinové sloučeniny; Endocytosis; transport proteinů; kyseliny indoloctové; kvartérní amoniové sloučeniny; Fluorescent Dyes; Cell Membrane; Indoleacetic Acids; endocytóza; Pyridinium Compounds; rostlinné proteiny; Plant Proteins; buněčná membrána; Protein Transport; buněčné linie; Arabidopsis